The Corsican shadow [large type] - Cussler, Dirk (Cussler, Clive. Dirk Pitt adventure, 2023)
"In May 1940, as the German army blitzes Europe and Parisians flee their city, the chief curator of the Musée de l'Armée is ordered to get a mysterious piece of cargo out of the country. When he arrives at the port of Le Havre and learns that his intended ship has been sunk, he places the object on a decrepit steamer that sails out under German fire. In the present day, National Underwater and Marine Agency Director Dirk Pitt is on a diving expedition in the English Channel when he discovers a cache of uncut diamonds on a shipwreck. When the diamonds are stolen, Pitt and the NUMA agency find themselves up against a murderous cabal that soon reveals far more destructive plans than mere theft. Vital water treatment facilities around the globe are being targeted-placing the world's population in grave peril. From the shadow of the Eiffel Tower to the depths of the Irish Sea to the islands of the Caribbean, only Dirk Pitt and his children, Summer and Dirk Jr., can locate the treasure that will preserve the soul of a nation...and save the world from catastrophe"--